Viruses and sumoylation: recent highlights - Boggio, Roberto (Curr Opin Microbiol, 2006)
Since its discovery in 1997, SUMO (small ubiquitin-like modifier) has been implicated in a range of activities, indicating that this protein is as important in the cell as ubiquitin is. Although it can function throughout the cell, it appears to be involved more in nuclear functions. The growing list of substrates that are covalently modified by SUMO includes many viral proteins; SUMO appears to facilitate viral infection of cells, making it a possible target for antiviral therapies. It therefore is important to understand how viruses manipulate the cellular sumoylation system and how sumoylation affects viral functions.